Faktor- Faktor Yang Mempengaruhi Permintaan Ibu Rumah Tangga Terhadap Sawi Organik Di Kota Malang - Andry Nggalihama (BiSTeK Pertanian, 2021)
Organic vegetables are foods that are environmentally friendly and healthy. This study aimed to determine the socio-economic factors on the demand housewives against organic mustard in Malang. This research was conducted in the Village Cemorokandang, District Kedung Cage Malang chosen deliberately because this location is one of the organic vegetable market and production center for organic vegetables (spinach, kale) in the city of Malang. The independent variables in this study are: aged housewife, homemaker education, number of household members, the price of organic vegetables are cabbage, collards non orgnik vegetable prices, expenditure housewives to buy vegetables. The dependent variable: the number of organic mustard purchased